2019
DOI: 10.1007/s00011-019-01215-1
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in the inflammatory background of angiogenesis in gynecological cancers

Abstract: A tumor growth depends on the potency of the tumor to support itself with nutrients and oxygen. The development of a vascular network within the tumor is key to its survival. The permanent contest between the tumor and its host involves tumor cells on one side and an immunological system and tissue stroma on the other. The angiogenesis is not only a specialty of the tumor, but it also depends on this complex multidirectional interaction. The most common gynecological cancers, cervical, endometrial and ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…In recent years, increasing evidence has shown that activation of inflammation is a crucial mechanism for the recurrence and metastasis of gynecological [ 3 , 4 ] and breast [ 5 , 6 ] cancers. Thus, inflammatory-related peripheral cells measured in routine blood test (such as neutrophils, lymphocytes, and platelets) and their derived index [including neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII, platelet count × neutrophil count/lymphocyte count)] may be potential prognostic biomarkers for gynecological and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence has shown that activation of inflammation is a crucial mechanism for the recurrence and metastasis of gynecological [ 3 , 4 ] and breast [ 5 , 6 ] cancers. Thus, inflammatory-related peripheral cells measured in routine blood test (such as neutrophils, lymphocytes, and platelets) and their derived index [including neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII, platelet count × neutrophil count/lymphocyte count)] may be potential prognostic biomarkers for gynecological and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence have showed that elevated NLR might be related to cancer growth and metastasis 19 , 20 , 27 , 42 . It is associated with poorer response to chemotherapy and radiotherapy, worse survival outcomes 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, HPV-driven carcinogenesis represents a commonly acknowledged example of how chronic inflammation caused by a persistent infection becomes a driving force for tumor development [105]. It is also well accepted that an inflammatory response can contribute to the development of a vascular network within the tumor [106], including lymphatic vascular network [107], and EMT [108]. Besides, the members of the interferon-mediated antiviral response (interferon-stimulated genes, ISG) may facilitate tumor-associated lymphangiogenesis and enhance lymphatic metastasis capabilities [109].…”
Section: Discussionmentioning
confidence: 99%